Association of IL‐10‐1082A/G polymorphism with cardiovascular disease risk: Evidence from a case–control study to an updated meta‐analysis - Shijuan Lu; Jianghua Zhong; Kang Huang; Honghao Zhou (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Previous studies have generated controversial results about the association of interleukin 10 (IL‐10) gene polymorphisms (−1082G/A) in the progression of cardiovascular disease (CVD). Therefore, this study processed a systemic meta‐analysis to verify this association. Methods The publication studies on the IL‐10 (−1082G/A) polymorphism and CVDs risk were obtained by searching PubMed and Embase databases. We analyzed the genotype data for meta‐analysis. The results were evaluated by odds ratios (ORs) and 95% confidence intervals (CIs). Meanwhile, our meta‐analysis was also performed sensitivity analyses, heterogeneity test, and identification of publication bias. Results The present meta‐analysis suggested that the risk with allele G is lower than with allele A for CVD. The G allele of IL‐10 (−1082) could increase the risk of CVDs in the 31 case–control studies for all genetic models. (OR = 1.10, 95% CI: 1.04–1.15 for the allele model A vs. G; OR = 0.87, 95% CI: 0.72–1.04 for the dominant model GG+AG vs. AA; OR = 1.03, 95% CI: 1.02–1.05 for the recessive model GG vs. AG + AA; OR = 1.06, 95% CI = 1.03–1.10 for the homozygote comparison model GG vs. AA; and OR = 0.88, 95% CI = 0.73–1.06 for the heterozygote comparison model AG vs. AA). Conclusions In genetic models, the association between the IL‐10 (−1082G/A) polymorphism and CVDs risk was significant. This meta‐analysis proposes that the IL‐10 (−1082G/A) polymorphism may serve as a risk factor for CVDs.